Build Your Own Equiluminance Helmet. (July 2017) - Connolly, Salammbo; Connolly, Denis; Cleary, Anne; Herman, Laura; Cavanagh, Patrick
A wearable 'helmet' version of the S cone isolating technique was constructed to explore vision at equiluminance. For my high school summer science project, I visited parks and streets while wearing the helmet and report that the helmet appears to have captured the main properties described for the large-scale, more cumbersome stage version.